Community-Based Design Research: Learning Across Generations and Strategic Transformations of Institutional Relations Toward Axiological Innovations. (2nd January 2016) - Bang, Megan; Faber, Lori; Gurneau, Jasmine; Marin, Ananda; Soto, Cynthia
Abstract: The socio-ecological challenges facing communities in the 21st century are building towards a critical conjuncture of history, culture, power, and profound inequity. Scholars working in the service of social transformation and improving the wellbeing of communities are calling for creative, deliberate, and consequential interventions. Tharp & O'Donnell (this issue) call for increased engagement between Cultural-Community Psychology and Cultural-Historical Activity Theory to lead this kind of call. Drawing from our experiences in community based design research, we argue for cultivating axiological innovations in research and interventions. We explore three examples including: critical historicity, inter-generational learning, and strategic transformations of institutional relations.